(3UjZ GdJehjd HGdeQGLYI (B/s - (3GdQHjYI, SYhO eMeOs ((3GdchjJ(B: s (3OGQ GdhQGbjf ddfTQ hGdJhRjY(B, s, 2001)
(3jbOe gPG GdcJGH bVjI ef bVGjG GdeGd GdYUQjI GdGSdGejI GdedMI bVjI HjY GdeQGHMI GdPj HOCJ JCNP ecGfJgG aj GbJUGOjGJ Gdjhe hJXgQ GjLGHjGJ Ydi GdeSJhi GdeMdj hGdYQHj hGdGSdGej hCNPJ JTgO CfXGQ GdGbJUGOjf GdjgG Ydi GdeSJhi GdYQHj hGdGSdGej , agPG GdLGfH aj GdGbJUGO GdGSdGej djS eJQhcG Ohf JYQja hHjGf deTQhYjI hJWhQ g aj GdbQhf GdGSdGejI GdeGVjI MJi UGQ cjGfG aj GdGbJUGO hGSG ef GSS hbhGYO JMGaX Ydjg ef Gf jJONd eY GbJUGOjGJ CNQi djSJ GSdGejI aJDKQ aj eSjQJg Cf jJhSY ajg Edi MO GdNOT Hg ajTc ef NdGdg hgfG jLH GHQGR eRGjG GbJUGOjGJ GdJehjd HGdeQGHMI HNeS eHGMK hgj (B1/ (3JYQja GdeQGHMI heTQhYjGJgG hTQhWgG (B2/ (3eQGMd JWhQ HjY GdeQGHMI (B3/ (3JWHjb GdeQGHMI GdeYGUQI hCMcGegG (B4/ (3GbJUGOjGJ GdJehjd HGdeQGHMI (B5/ (3GdGSGdjH GdebJQMI dJWHjb GdeQGHMIs
Keywords: (3GdHjY HGdeQGHMIs; (3eQGLYIs